Intravenous thrombolysis for the management of acute ischemic stroke in patients therapeutically anticoagulated with heparin: A review - Neves, Gabriel; Lee, Jeannie; Bueso, Tulio; Montalvan, Victor; Iskandir, Marina; Shurmur, Scott; Kim, Jongyeol (Clinical neurology and neurosurgery, 2021)
•The minority of patients who suffer an acute ischemic stroke are eligible for fibrinolytic therapy.•Many of the exclusion criteria for fibrinolytic therapy are not well established.•Patients on heparin therapy are excluded from fibrinolytics.•Heparinized patients have successfully been treated with fibrinolytics for the management of acute ischemic stroke. Intravenous thrombolysis (IVT) with alteplase is effective in acute ischemic stroke (AIS). However, its use rate remains low due to the many exclusion criteria. Recent guidelines recommend excluding patients suffering AIS with an elevated aPTT secondary to heparin exposure from receiving IVT. The purpose of this review is to explore the safety and efficacy of IVT in patients therapeutically anticoagulated with heparin. We also propose a treatment algorithm for IVT in patients with AIS that are therapeutically anticoagulated with heparin. We performed a systematic review of PubMed and Embase through March 2020 to identify the literature regarding AIS in patients exposed to heparin, followed by IVT treatment, emphasizing safety, efficacy, and clinical outcome using PRISMA guidelines. We included thirteen articles in the final analysis, including three retrospective studies, two observational studies, one randomized trial, five case reports, and two case series. There is limited information about the off-label use of IVT in patients with elevated aPTT. Patients with AIS are excluded from IVT if they have recent exposure to heparin. Our review indicates that this population of patients may benefit from IVT as the cases of active bleeding after IVT are few, and functional outcomes are favorable in the long term suggesting that IVT in therapeutically anticoagulated patients may be safe and efficacious.